Unraveling the ethical, legal, and social implications of neurobiobanking and stroke genomic research in Africa: a studyprotocol of the African neurobiobankfor precision stroke medicine ELSI project (2020)
The ethical, legal, and social implications (ELSI) of emerging neurobiobanks and data resources are unclear in an African scientific landscape with unique cultural, linguistic, and belief systems. The overarching goal of the African Neurobiobank for Precision Stroke Medicine–—ELSI Project is to identify, examine, and develop novel approaches to address ELSI issues of biobanking and stroke genomic research in sub-Saharan Africa (SSA). To accomplish the goal we will (1) explore knowledge, attitude, perceptions, barriers, and facilitators influencing ELSI issues related to biobanking and stroke genomic research; (2) use information obtained to craft a community intervention program focused on ELSI issues; and (3) build capacity and careers related to genomics and biobanking for effective client/community engagement while enhancing regulatory, governance, and implementation competences in biobanking science in SSA. A community-based participatory research and mixed-methodological approach, focused on various levels of the social ecological model, will be used to identify and examine relevant ELSI issues. Contextual intervention tools, platforms, and practices will be developed to enhance community understanding and participation in stroke biobanking and genomics research activities while facilitating enduring trust, and equitable and fair utilization of biobanking resources for genetic and trans-omics research. A concurrent capacity building program related to genetic counseling and biobanking will be implemented for early career researchers. The huge potential for neurobiobanking and genomics research in Africa to advance precision medicine applicable to stroke and other neurological disorders requires addressing ELSI challenges while building sustainable research, career, and regulatory capacities in trans-omics and biobanking science.